2014
DOI: 10.1016/j.aller.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of zinc in asthmatic patients: A case–control study

Abstract: As for high rate of hypozincemia in the asthmatic children, evaluation of serum zinc level in asthmatic children could be suggested, while zinc substitution in the diet of those with hypozincemia could be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 9 publications
1
16
2
Order By: Relevance
“…Zinc deficiency may exacerbate airway inflammation in asthma. 47 Some studies show an association between low zinc levels and asthma, [48][49][50][51][52] while others contradict these findings, [53][54][55][56] and systematic review evidence is lacking. One study found no relationship between allergic rhinitis and plasma zinc and another study found no relationship between allergic rhinitis and dietary zinc intake.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc deficiency may exacerbate airway inflammation in asthma. 47 Some studies show an association between low zinc levels and asthma, [48][49][50][51][52] while others contradict these findings, [53][54][55][56] and systematic review evidence is lacking. One study found no relationship between allergic rhinitis and plasma zinc and another study found no relationship between allergic rhinitis and dietary zinc intake.…”
Section: Discussionmentioning
confidence: 99%
“…24 Later study by Khanbabaee and colleagues also found that the mean serum zinc level in pediatric asthma patients was 70.5 mg/dL, and that 42% of patients were hypozincemic. 17 They found that there was a significant association between zinc level and severity of disease. Both studies were conducted to evaluate zinc status, using a cross-sectional study design, during non-exacerbation periods.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 On the contrary, the antiinflammatory, anti-apoptotic effects of zinc on respiratory epithelium rather than smooth muscles of the respiratory tract make it a better prophylactic agent than a bronchodilator drug. 3,4 However, our idea behind screening bronchodilator effect of zinc in acute attack of asthma was based on the inhibitory effect of magnesium on NMDA receptors. Relaxation of the smooth muscles by inhibition of calcium channels by magnesium is basically an indirect effect mediated through inhibition of NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…This is because apart from the evidences of its deficiency in bronchial asthma patients, zinc has shown cellular and molecular level antiasthma effects. [3][4][5] Daily supplementation of low dose of zinc was proven to be beneficial at least in terms of reduction in severity of clinical signs and symptoms of bronchial asthma in children. 6 Unlike zinc, the deficiency of magnesium in asthma patients was not found in a clinical study but has shown the weak but significant effects in treatment of acute asthma.…”
Section: Introductionmentioning
confidence: 99%